2003
DOI: 10.1038/nature02039
|View full text |Cite
|
Sign up to set email alerts
|

Plant recognition of symbiotic bacteria requires two LysM receptor-like kinases

Abstract: Although most higher plants establish a symbiosis with arbuscular mycorrhizal fungi, symbiotic nitrogen fixation with rhizobia is a salient feature of legumes. Despite this host range difference, mycorrhizal and rhizobial invasion shares a common plant-specified genetic programme controlling the early host interaction. One feature distinguishing legumes is their ability to perceive rhizobial-specific signal molecules. We describe here two LysM-type serine/threonine receptor kinase genes, NFR1 and NFR5, enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
808
0
26

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,049 publications
(850 citation statements)
references
References 46 publications
16
808
0
26
Order By: Relevance
“…It has been proposed that the LysM-type cell-wall binding domain binds non-covalently to peptidoglycan of various gram-positive bacteria [12]. The LysM motif has also been found in a number of eukaryotic proteins [10], and it was recently demonstrated that LysM domains are involved in recognition of symbiotic bacteria by the roots of plants [13][14][15]. In L. lactis, following secretion of the AcmA cell-wall hydrolase, the PA directs the protein to the cell wall.…”
Section: The Protein Anchormentioning
confidence: 99%
“…It has been proposed that the LysM-type cell-wall binding domain binds non-covalently to peptidoglycan of various gram-positive bacteria [12]. The LysM motif has also been found in a number of eukaryotic proteins [10], and it was recently demonstrated that LysM domains are involved in recognition of symbiotic bacteria by the roots of plants [13][14][15]. In L. lactis, following secretion of the AcmA cell-wall hydrolase, the PA directs the protein to the cell wall.…”
Section: The Protein Anchormentioning
confidence: 99%
“…Here, we detected a chitinase (predgene 000254), a family of enzymes known for their role in resistance to pathogens (Punja and Zhang 1993;Grover 2012). We also discovered a gene involved in recognition of symbiotic bacteria (LysM receptor-like kinase, predgene 002974) which notably enables the model legume Lotus japonicus to recognize its bacterial symbiont Radutoiu et al 2003;Ryals et al 2008). Symbiotic nitrogen fixation is a specific feature of legumes, and nutrient availability largely varies across microhabitats (Ferry et al 2010).…”
Section: )mentioning
confidence: 99%
“…Mutations in En 1314 and En 1282 soybeans were found in the NFR1 gene, which is known to be responsible for a LysM-type receptor kinase for Nod factor recognition (Radutoiu et al, 2003 Masaki Hayashi (National Institute of Agrobiological Sciences, Tsukuba, Japan), personal communication). A mutation in En 6500 was found in the GmNARK (NTS1) gene (Nishimura et al, 2002), which mediates systemic autoregulation of nodulation (Searle et al, 2003), and Sakukei 4 is a descendant with a hypernodulating phenotype that was derived from En 6500 (Matsunami et al, 2004).…”
Section: Plant Materials and Field Experimental Designmentioning
confidence: 99%